Manajemen Kompetensi Lulusan (Studi Kasus di Madrasah Bertaraf Internasional Amanatul Ummah Mojokerto) - Agus Prastiyo; Sigit Priyo Sembodo (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2022)
This article aims to describe the competency management of graduates at MBI Amanatul Ummah Mojokerto. The research method that has been used is qualitative with a case study approach. Retrieval techniques and observation, interviews and documentation. Competency Management Graduates at MBI Amanatul Ummah Pacet Mojokerto, the researchers concluded, a) Conducted selection based on general ability, b.) tested with their religious knowledge, c.) tested for formal competence in mathematics, physics, biology, English and psychological tests, d.) matriculation for equalizing Arabic, English, writing pegon letters and making Olympic classes for class 10 f.) special class 11-12, in class 12 it is focused on foreign classes, official class, and UTBK class for domestic.